PENGARUH PERCEIVED USEFULNESS DAN TRUST TERHADAP KEPUASAN KONSUMEN PADA E- COMMERCE SHOPEE - Latifah, Nunuk; Widayani, Anna; Normawati, Rani Arifah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
The purpose of this study is to analyze and explain the effect of perceived usefulness and trust on consumer satisfaction of Shopee e-commerce. This research conducted in Indonesia that targeted Shopee consumers. Data were collected from the survey by distributing questionnaires to the research respondents. The sample consisted of 86 people selected by a random sampling technique. Data were analyzed using multiple linear regression. Results showed that perceived usefulness and trust have a positive and significant effect on consumer satisfaction. The results of this study also proved that Shopee users assess that the perceived usefulness of the e-commerce applications could facilitate convenience during the online transaction. Meanwhile, trust, in the form of guaranteed transactions and recommendations and ratings from consumers, is a form of support and services provided by Shopee to build consumer trust in Indonesia. Keywords: customer satisfaction, e- commerce, perceived usefulness, Shopee, trust